2017
DOI: 10.1002/pon.4510
|View full text |Cite
|
Sign up to set email alerts
|

Protection motivation theory in predicting intention to receive cervical cancer screening in rural Chinese women

Abstract: PMT can be used as guidance to investigate cervical cancer screening intentions among rural women in China with focus on cancer knowledge, some demographic factors, and awareness of and previous experience with screening. These findings, if verified with longitudinal data, can be used for intervention program development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 41 publications
7
41
5
2
Order By: Relevance
“…Supported by findings from the published cross‐sectional studies of our own and others, this longitudinal study has documented the rate of rural women's participation in cervical cancer screening, confirmed the association of a group of factors (eg, demographic, knowledge of cervical cancer screening) with screening uptake, and demonstrated the utility of PMT in predicting subsequent cancer screening behavior among a large sample of women in rural China. Findings of this study update our knowledge on screening participation behavior, and add new evidence supporting cervical cancer prevention intervention programs to enhance screening for this group of rural women with high cervical cancer incidence and mortality.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Supported by findings from the published cross‐sectional studies of our own and others, this longitudinal study has documented the rate of rural women's participation in cervical cancer screening, confirmed the association of a group of factors (eg, demographic, knowledge of cervical cancer screening) with screening uptake, and demonstrated the utility of PMT in predicting subsequent cancer screening behavior among a large sample of women in rural China. Findings of this study update our knowledge on screening participation behavior, and add new evidence supporting cervical cancer prevention intervention programs to enhance screening for this group of rural women with high cervical cancer incidence and mortality.…”
Section: Discussionsupporting
confidence: 63%
“…Likewise, population‐based studies indicated that perceived severity can significantly predict screening uptake among women, although inconsistent findings are occasionally reported . In a previous study with cross‐sectional data, we observed that perceived severity of cervical cancer was positively associated with intention to participate in cervical cancer screening, and response cost was negatively associated with participation intention among rural women in China …”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations